Analisis Pelaksanaan Penyanderaan Penanggung Pajak Pada KPP Pratama Pematang Siantar Melalui Perkara Gugatan Nomor 29/PDT.G/2021/PN.Pms - Charly Hasibuan; Primandita Fitriandi (JURNAL PAJAK INDONESIA, 2022)
Tax revenues used for national development must continue to be carried out by the government to improve the economy of a prosperous and prosperous society. Therefore, the contribution of tax revenue must continue to be optimized. Optimal tax revenue must be supported by safeguarding state revenues through taxes, namely by collection actions. There is a lawsuit registered at the Pematangsiantar District Court number 29/Pdt.G/2021/PN.Pms filed by the Tax Insurer "H" regarding the act of taking hostage according to the Tax Insurer who has committed an unlawful act. The research method that the author uses is a qualitative approach with collect data and interpret phenomena for analysis. The  data collection technique that the author uses is to   conduct field studies and literature studies. The author's field study was carried out by coming directly to the Pematang Siantar KPP Pratama by interviewing one of the officials in the Billing Section. Literature study the author conducted by studying literature references. The results of research on the lawsuit number 29/Pdt.G/2021/PN.Pms, that Defendants I, II, III, and IV have never committed acts of abuse of authority in the form of exceeding their authority in carrying out hostage taking against Tax bearer "H". The Tax Insurer has violated the provisions of bringing the communication device into the detention room